(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article focuses on the formation and formation of teaching skills in the primary education system today, the use of modern methods and technologies in this process, and at the same time the education of students. and a number of tasks have been identified.